Tuberculosis in the twentieth century: time-series mortality in São Paulo, Brazil, 1900-97 - José Leopoldo Ferreira Antunes; Eliseu Alves Waldman
The objective of this study was to characterize tuberculosis mortality trends in the Municipality of São Paulo, Brazil, from 1900 to 1997. Standardized tuberculosis mortality rates and proportional mortality ratios were calculated and stratified by gender and age group based on data provided by government agencies. These measures were submitted to time-series analysis. We verified distinct trends: high mortality and a stationary trend from 1900 to 1945, a heavy reduction in mortality (7.41% per year) from 1945 to 1985, and a resumption of increased mortality (4.08% per year) from 1985 to 1995. In 1996 and 1997 we observed a drop in tuberculosis mortality rates, which may be indicating a new downward trend for the disease. The period from 1945 to 1985 witnessed a real reduction in tuberculosis, brought about by social improvements, the introduction of therapeutic resources, and expansion of health services. Recrudescence of tuberculosis mortality from 1985 to 1995 may reflect the increasing prevalence of Mycobacterium and HIV co-infection, besides loss of quality in specific health programs.